Therapeutic Use of Non-invasive Brain Stimulation in Dystonia - Quartarone, Angelo; Rizzo, Vincenzo; Terranova, Carmen; Cacciola, Alberto; Milardi, Demetrio; Calamuneri, Alessandro; Chillemi, Gaetana; Girlanda, Paolo (Frontiers in Neuroscience, 2017)
Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) are non-invasive methods for stimulating cortical neurons that have been increasingly used in the neurology realm and in the neurosciences applied to movement disorders. In addition, these tools have the potential to be delivered as clinically therapeutic approach. Despite several studies support this hypothesis, there are several limitations related to the extreme variability of the stimulation protocols, clinical enrolment and variability of rTMS and tDCS after effects that make clinical interpretation very difficult. Aim of the present study will be to critically discuss the state of art therapeutically applications of rTMS and tDCS in dystonia.